Proceedings of the Twenty-Third Annual ACM Symposium on Principles of Distributed Computing 2004
DOI: 10.1145/1011767.1011818
|View full text |Cite
|
Sign up to set email alerts
|

The weakest failure detectors to solve certain fundamental problems in distributed computing

Abstract: We determine the weakest failure detectors to solve several fundamental problems in distributed message-passing systems, for all environments -i.e., regardless of the number and timing of crashes. The problems that we consider are: implementing an atomic register, solving consensus, solving quittable consensus (a variant of consensus in which processes have the option to decide 'quit' if a failure occurs), and solving non-blocking atomic commit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
8

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 26 publications
(64 reference statements)
0
99
0
8
Order By: Relevance
“…Recall that ♦S is the weakest to solve the problem only in majority-correct environments [29]. In environments where an arbitrary number of processes may crash, the weakest failure detector for the problem is a stronger oracle (♦S, Σ) [15]. Given that ♦S encapsulates some fairness constraints, and Σ can be implemented in an asynchronous system with majority correct, we conjecture that Σ and majority-correct encapsulate equivalent fairness constraints in the system.…”
Section: Open Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall that ♦S is the weakest to solve the problem only in majority-correct environments [29]. In environments where an arbitrary number of processes may crash, the weakest failure detector for the problem is a stronger oracle (♦S, Σ) [15]. Given that ♦S encapsulates some fairness constraints, and Σ can be implemented in an asynchronous system with majority correct, we conjecture that Σ and majority-correct encapsulate equivalent fairness constraints in the system.…”
Section: Open Questionsmentioning
confidence: 99%
“…For example, consider wait-free consensus. The weakest failure detector for this problem in asynchronous shared-memory systems is Ω [29] whereas the weakest failure detector to solve the same problem in message-passing systems is (Ω, Σ); 1 that is, process have access to two failure detectors Ω and Σ [15]. Similarly, for solving wait-free k-set agreement, the weakest failure detector in shared-memory systems is anti-Ω k 2 [23], but the weakest failure detector in message-passing systems remains an open problem [8,9].…”
Section: Weakest Models For Failure Detectors In Shared Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the failure detector class denoted Ω is the weakest failure detector class that allows consensus to be solved in message-passing asynchronous systems where a majority of processes never crash [9]. It has also been shown that the pair (Σ, Ω) is the weakest failure detector class when any number of processes may crash [14,15]. (These failure detector classes are precisely defined later in the paper.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the information provided about the failure of a process might not be perfect. It is common to ask what information about failures is necessary and sufficient to circumvent some specific impossibility, e.g., consensus [3], atomic commit [6], mutual exclusion [7], etc.…”
Section: Introductionmentioning
confidence: 99%